Isolation and characterisation of a MYB transcription factor associated with epigallocatechin-3-gallate biosynthesis in Camellia sinensis L. Issue 1 (2nd January 2019) - Zheng, Shizhong; Lin, Yuling; Lai, Zhongxiong; Lin, Jinke
ABSTRACT: Epigallocatechin-3-gallate (EGCG) is a major bioactive ingredient of tea polyphenols, and a MYB transcription factor (TF) named CS_MYB regulated EGCG biosynthesis in tea plant. We isolated CS_MYB from Camellia sinensis L. '1005' cultivar. Bioinformatics analysis showed that the CS_MYB protein was 1R-MYB with a single repeat, and was localised to the nucleus, consistent with the result of sub-cellular localisation analysis. Phylogenetic analysis revealed that the CS_MYB protein clustered to the same branch as AT5G56840.1 of Arabidopsis thaliana, suggesting that if the two proteins had similar functions, then CS_MYB may be a transcriptional repressor. A comparison of the CS_MYB's expression level and EGCG content at different developmental leaf stages in three cultivars ('1005', its parental plants 'Huangdan' and 'Fuyun 7') was conducted. The results revealed that the '1005' cultivar displayed heterosis. Moreover, CS_MYB 's expression was observed to vary, with each cultivar showing a similar trend: fourth leaf > second leaf > bud, while changes in EGCG content exhibited the opposite trend. Thus, CS_MYB's expression may negatively regulate EGCG biosynthesis in tea plants.